Changes in Chemokine Receptor Expression of Regulatory T Cells after Ex Vivo Culture - Chakraborty, Rikhia (2012)
By controlling and limiting inflammatory conditions, naturally occurring regulatory T cells (nTregs), defined as circulating CD4(+)CD25(bright)FoxP3(+) cells, play critical roles in maintaining tolerance and preventing autoimmunity, and thus have tremendous potential for adoptive immunotherapy. Because they represent a scanty subset of the CD4(+) T lymphocyte subset, several approaches have been developed to isolate and expand ex vivo polyclonal Tregs. However, one limitation of the functional analyses performed on these cultured Tregs is the incomplete characterization of their tissue trafficking properties. As this aspect provides crucial information for their therapeutic effects, we have here explored the chemokine receptor expression profile and function of Tregs cultured ex vivo with validated expansion protocols. Our data show that ex vivo cultured Tregs retained the expression of CCR7 but dramatically down regulated CCR5 as compared to freshly isolated Tregs. The differential chemokine receptors expression pattern corroborated with their respective steady state messenger RNA expression and also their migration towards specific chemokines. Our analyses suggest that ex vivo cultured Tregs may display impaired or suboptimal migration to the inflamed tissues releasing RANTES and MIP-1α chemokines.